“We have no safety at all”: insecurity and continuous traumatic stress among Palestinian adolescents in East Jerusalem - Zedan, Heba F. (Frontiers in Psychology, 2025)
This research was completed in collaboration with the Children and Youth Advisory Group: Mays, Nada, Amro, Sajida, Kinan, Rama, and Qamar.IntroductionChildren and youth in conflict zones are often exposed to persistent sociopolitical stress that undermines their rights to protection and development. This study explores how Palestinian adolescents in occupied East Jerusalem experience and respond to continuous traumatic stress amid intensified political violence during the ongoing Gaza war.MethodsUsing a participatory research approach, an advisory group of youth co-researchers contributed to study design, ethics, data collection, and analysis. In-depth interviews were conducted with 24 Palestinian youth aged 12–19, alongside eight adult parents and professionals.ResultsReflexive thematic analysis revealed six interconnected themes: (1) Perpetual threat in everyday spaces; (2) Adaptive hypervigilance; (3) Collective and intergenerational transmission of stress; (4) Emotional suppression and helplessness; (5) Normalization of abnormality; and (6) Distrust in protective systems. The findings demonstrate how structural violence is internalized, embodied, and transmitted across generations, creating a persistent emotional climate of fear and insecurity.ConclusionThis study calls for trauma frameworks that move beyond episodic models to address cumulative, politically rooted stressors that violate children’s rights under international law. Policies must prioritize rights-based interventions, including accessible psychosocial support and protective legal frameworks that counter systemic oppression, surveillance, and discrimination. Integrating children’s lived experiences and agency into service design and delivery is highly recommended.